Enhancing Nature Connection and Positive Affect in Children through Mindful Engagement with Natural Environments - Barrable, Alexia; Booth, David; Adams, Dylan; Beauchamp, Gary (International Journal of Environmental Research and Public Health, 2021)
Nature connection, which describes a positive relationship between humans and the rest of nature, has been recognised as a worthwhile goal of all education. Given its association with wellbeing, as well as the fact that it can predict ecological behaviours in children, there have been several calls for it to become central to environmental education, and an important tool in tackling climate change. Previous research has reported the success of short-term interventions in increasing nature connection in children, but to date no empirical studies have looked at how mindful engagement with nature can promote both nature connection and positive affect. This study took place in a nature reserve in Wales and included n = 74 children, aged 9–10, who took part in three mindful activities. Pre- and post- measures included nature connection and positive/negative affect. Analysis showed a significant small to medium effect of the activity on nature connection. Moreover, positive affect significantly increased post-activity, while negative affect showed a small decrease.